Lima Andina: Una herramienta digital para la historia de la migración interna en Perú - Durston, Alan (Pontificia Universidad Católica del Perú, 2026)
This note presents a digital platform containing more than six thousand notices published by internal migrant associations in the newspaper El Comercio between 1906 and 1933, allowing for a systematic study of the presence and dynamics of these associations in Lima in the early twentieth century. Based on a database that records 488 organizations and their notices, the platform offers search and visualization tools useful for exploring patterns of migration, sociability, and political participation. The note describes the methodological decisions and collaborative process behind the project, highlighting both the challenges of digital work and its potential for future historicalresearch.

Esta nota presenta una plataforma digital con más de seis mil avisos publicados por asociaciones de migrantes internos en el diario El Comercio entre 1906 y 1933, permitiendo estudiar de manera sistemática la presencia y las dinámicas de estas asociaciones en Lima a comienzos del siglo XX. A partir de una base de datos que registra 488 organizaciones y sus avisos, la plataforma ofrece herramientas de búsqueda y visualización útiles para explorar patrones de migración, sociabilidad y participación política. La nota describe las decisiones metodológicas y el proceso colaborativo detrás del proyecto, destacando tanto los desafíos del trabajo digital como su potencial para futuras investigaciones históricas.
Lima Andina: A digital tool for the history of internal migration in Peru
Keywords: Digital history; Digital humanities; History of Peru; History of Lima; Internal migration; Migrant associations; Historia digital; Humanidades digitales; Historia de Perú; Historia de Lima; Migración interna; Asociaciones de migrantes; https://purl.org/pe-repo/ocde/ford#6.01.01